Arthroscopic Excision of Acetabular Osteoid Osteoma: Computer Tomography–Guided Approach - Tamam, Cüneyt (Arthrosc Tech, 2015)
Osteoid osteoma is a benign osteoblastic tumor that occurs in the subcortical shaft and metaphysis of the long bones of the lower extremities; however, intra-articular lesions are also possible. Intra-articular osteoid osteomas are rare, and clinical symptoms are often less specific and, thereby, may lead to misdiagnosis. The definitive treatment for osteoid osteoma is the excision of the nidus. We present the case of a 23-year-old man with a 4-year history of right anterior hip pain, subsequently diagnosed with a subarticular osteoid osteoma located in the right anterior acetabulum. Hip arthroscopic excision of the juxta-articular osteoid osteoma is presented as an effective treatment, with the advantage of less potential damage to normal bone and cartilage, as well as the additional benefits available with hip arthroscopy.